أهمية التسويق الالكتروني في تعزيز المسؤولية الاجتماعية للمنظمات الخيرية -دراسة ميدانية بجمعية كافل اليتيم بريكة- - معيريف, عقبة; ميمون, نبيلة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الورقة البحثية إلى إبراز أهمية التسويق الالكتروني داخل المنظمات الخيرية من أجل تعزيز مسؤولياتها الاجتماعية الملقاة على عاتقها، وقد تم اختيار جمعية كافل اليتيم بريكة لإجراء الدراسة الميدانية نظرا لطبيعة نشاطها الاجتماعي والموجه أساسا لخدمة فئة معينة من المجتمع وهي الأرملة واليتيم، حيث تم توزيع استبيان الكتروني على عينة من جمهور الجمعية (محسنين، أعضاء، مستفيدين، متابعين) والذين يمثلون عملاء بالنسبة لها، وقد بلغت عينة الدراسة 96 مفردة. تم التوصل إلى ضرورة انتهاج أسلوب التسويق الالكتروني من خلال جذب العملاء وتعريفهم بمختلف المشاريع الخيرية، مع خلق تواصل دائم ومستمر معهم، ثم مشاركتهم لمعرفة رغباتهم وتفضيلاتهم، إضافة إلى جمع معلوماتهم الشخصية لمعرفة مواقفهم وسلوكياتهم، وفي الأخير الاحتفاظ بهم ودفعهم إلى تكرار المساهمة في المشاريع الخيرية وهذا لضمان الاستمرارية في تبني هاته المشاريع ذات الأبعاد الاجتماعية، والصحية، والتربوية، والتكوينية. This paper aims to explore the importance of e-marketing within charitable organizations to strengthen their social responsibilities. The Bail Orphan Association Barika was selected to conduct the field study due to the nature of its social activity, which is primarily directed at serving a particular category of society, the widow and orphan. An electronic questionnaire was distributed to a sample of the society's audience. (Enhancers, members, beneficiaries, followers) who represent clients for them, with a sample study of 96 individuals. The need to adopt an electronic marketing approach by attracting clients and introducing them to various charitable projects, creating constant and continuous communication with them, then sharing their desires and preferences, as well as collecting their personal information to know their attitudes and behaviors, and finally retaining them and prompting them to repeat contributions to charitable projects to ensure continuity in adopting these projects with social, health, educational and formative dimensions.
The importance of e-marketing in promoting the social responsibility of charitable organization The Association of Kafil Alyatim in barika province: case study
مقال
Keywords: التسويق الالكتروني، المسؤولية الاجتماعية، المنظمات الخيرية، جمعية كافل اليتيم بريكة; E-Marketing, Social Responsibility, Charitable Organizations, Bail Orphan Society Barika